Cost-effectiveness of human papillomavirus (HPV) vaccination in Tunisia: a modelling study - Mohamed Hsairi; Olfa Jaidane; Khedija Meddeb; Hyem Khiari; Karima Makni (BMJ Open)
Objectives The objective of this study is to assess the cost utility of the implementation of the human papillomavirus (HPV) vaccination programme in Tunisia in addition to the current cytology screening strategy. This study is very important to guide health policy decision-makers and to help them allocate their scarce healthcare resources.Design We used a previously described Markov model on the Online Cost Effectiveness Analysis tool programmed with R Software. The Markov cohort model was used to simulate the natural history of HPV infection and cervical cancer for a cohort of 100 000 females aged from 10 to 84 years. The model was calibrated with Tunisian parameters to calculate the long-term health benefits and costs of different cervical cancer preventive strategies in Tunisia.Outcome measures The primary outcome was the incremental cost-effectiveness ratio (ICER) of the implementation of HPV vaccination to the current cytology screening strategy to fight against cervical cancer. The ICER was calculated per life-years saved and per quality-adjusted life-year (QALY) gained, expressed in 2020 US$. Thresholds were fixed at one to three times the gross domestic product (GDP). One-way sensitivity analyses were carried out concerning the coverage rate of the cytology screening and vaccination as well as for the vaccination cost and doses.Results Compared with screening alone, the combined strategy predicted an ICER of US$1920.8 year of life saved and US$2239.3/QALY which is still lower than the GDP per capita of Tunisia in 2020 (US$3319). Sensitivity analysis showed that the cost-effectiveness of adding vaccination to the existing screening programme did not exceed the GDP per capita by varying the cost per dose upwards to US$45 (ICER would be US$2910/QALY) and vaccination coverage up to 100% (ICER of US$3245/QALY). However, the combined strategy exceeds the GDP per capita threshold when the cytological screening coverage rises to 70%, causing the ICER to rise to US$4787/QALY.Conclusion This study showed that compared with screening alone, the implementation of HPV vaccination in addition to the current cytology screening programme in Tunisia would be considered cost-effective on the basis of the threshold GDP per capita. Improvement of the current screening programme itself also remains important and provides further potential to achieve optimal cervical cancer prevention strategies.